Ecocritcism On Kumandra as Environmental Sustainability in Raya And The Last Dragon - Sri Wulan; Nurhasanah; Zulfan Sahri (Universitas Tidar, 2023)
There is a harmonious relationship between the environment and humans depicted in the film Raya and the Last Dragon. A good environmental lesson is represented through Kumandra. Therefore, This study aims to explore Kumandra as a symbol of environmental sustainability in the film. The analysis was carried out based on the theory of Ecocritism. The theory is applied to find out the characters’ harmonious relationship with nature. The harmonious life is symbolized by the place, Kumandra. Data collection was done by qualitative descriptive method. The results of the analysis show that Kumadra is illustrated as a place where the community can maintain a harmonious life with nature. In Kumandra, the community is depicted as maintaining environmental harmony and balance. Although, Kumandra has been divided due to greed and the struggle for dragon’s gems, Benja and Raya still struggle to make all tribes return to what they used to be, namely Kumandra. Living in harmony in Kumandra brings peace, prosperity and unity for the people. It can be concluded that there are environmental lessons delivered by the film Raya and the Last Dragon.